Respuesta :

Answer: a = [tex]\frac{W-3b+4}{6}[/tex]

Step-by-step explanation:

W = 3(2a + b) - 4

W = 6a + 3b - 4

W - 3b + 4 = 6a

[tex]\frac{W-3b+4}{6}[/tex] = a

iiMGii
Let's write out the equation & begin by fully simplifying the right-hand side.

W = 3 ( 2a + b ) - 4
W = 6a + 3b - 4

Now, let's place (a) & it's co-efficient on the left-hand side & the (W) on the right-hand side in order to begin making (a) the subject.

6a = W - 3b + 4

From this, we can simply solve for (a) to find our solution.

a = ( W - 3b + 4 ) / 6
OR
a = ( 1 / 6 ) ( W - 3b + 4 )